Gênero e Religião: Olhares a partir da experiência religiosa de fiéis e ex-fiéis de igrejas evangélicas da cidade de Uberlândia/MG - Oliveira, Alesca Prado de (2019)
This essay has, as a main objective, to analyze the gender representations in the religious context, in relation to the perception and experience among the faithful and dissidents of evangelical organizations of the city of Uberlândia / MG. From an comprehensive and interpretative phenomenological perspective, it was considered the way that are produced the gender representations in the social spaces experienced by the surveyed women, from their constructions in the religious arrangement. The methodological approach includes methodologies such as bibliographical and semi-structured interviews, conducted with fifteen women residents of city of Uberlândia-MG who have presented in the course of their experiences, trajectory in the evangelical environment. The selection of actors took place between July and August 2018 and the interviews were conducted in the months of September and October, been the transcriptions concluded in November 2018. The synthesized results present the similarities between the women insertions into the religious organizations, highlighting the fundamental influence exercised by the family arrangement. They also point small changes that took place in the interest of evangelical institutions on the gender agreement, and in this regard, the ruptures that occurred from the unconformity with established practices.